Excursion to Youth Land with Jeppe Kristensen - Krøgholt, Ida; Exe Christoffersen, Erik (Peripeti, 2023)
Interview with Kristensen by Christoffersen and Krøgholt. Kristensen reflects on the process of Youth (Ungdom) focusing and on how the company created ownership for the young participants, to give agency as co-developers of the performance’s various spaces.